Infrastructural Aspects of Intensification of Entrepreneurial Activity as A Vector of Modern Global Economy Development - Tatiana Litvinova (European Scientific Journal, ESJ, 2017)
The problem of the research consists in the fact that despite the importance and significance of the infrastructure, it does not fully satisfy the needs of modern international business by quantitative (growing deficit) and qualitative (quick aging) characteristics. The working hypothesis of the research is the proprietary hypothesis that the cause of the existing situation and emergence of the problem is presence of contradictions in development of infrastructure of entrepreneurship in the global markets. The purpose of the article is to verify the offered hypothesis, to determine contradictions in entrepreneurship’s infrastructure in the global markets, and to determine their influence on development of international business. Methodology of the research is based on the use of the method of systemic and problem analysis, analysis of causal connections, synthesis, induction, deduction, formalization, and method of modeling of socio-economic systems for developing the model of development of entrepreneurship’s infrastructure in the global markets. Modern entrepreneurship’s infrastructure in the global markets is peculiar for systemic contradictions related to deepening of the gap between level of development of entrepreneurship’s infrastructure in developed and developing countries with increase of globalization and integration processes in the world economy, preservation of state regulation’s domination in the processes of creation and functioning of the main objects of entrepreneurship’s infrastructure, in spite of common market conditions, and simultaneous belonging of entrepreneurship’s infrastructure to public and private goods. The determined contradictions influence negatively the development of international business, causing and stimulating strengthening of underrun of the current level and possibilities of the global business infrastructure from actual needs of international entrepreneurship. This problem could be solved with the author’s model of development of entrepreneurship’s infrastructure in the global markets, which is based on the mechanism of public-private partnership and the corresponding recommendations.